PERAN HUKUM INTERNASIONAL DALAM MENEKAN PENGARUH EMISI SEKTOR PENERBANGAN TERHADAP LAJU PERUBAHAN IKLIM - Leony Marcha Rotua Cahaya Pardede (Faculty of Law Universitas Sebelas Maret, 2022)
Aviation emission as a factor in increasing and distribution of Greenhouse Gasses emission is a contributor to climate change and are expected to increase from 3% to 15% in 2050 if no international standard precautions are applied. Therefore, there is a need for regulations to be put in place to control aviation emissions. This legal research aims to describe the role of international law in efforts to reduce emission from aviation sector, as well as the enforcement imposed on countries to control emissions. Using a legal approach, the author examines how the Chicago Convention, the Kyoto Protocol, and the Paris Agreement regulate aviation emissions. The results of this study indicate that aviation emission are regulated in two international regimes, namely the International Civil Aviation regime and the Climate Change Regime, but with the enactment of these two regimes, there is still an increase in aviation emissions from countries by the year 2019. Therefore, a new and more structured steps are needed to reduce emissions from the aviation sector.